KAJIAN YURIDIS TENTANG KETENTUAN PRODUKSI DAN IJIN PEREDARAN OBAT TRADISIONAL BERKAITAN DENGAN PERLINDUNGAN KONSUMEN - Rana Dananjaya, A. A. Gde; M. E. Purwani, Sg. Putri (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 06, Juli 2013)
The paper entitled jurisdical study about production regulation and permit of traditionalmedicine related with consumer protection. This paper aims to know and understand about theterms of production regulation and distribution of traditional medicine. By using normativeresearch to find out the rule of law, principles of law, and legal doctrines to obtain solution tothe problems faced as well as to discuss lifestyle trends that led to the use / consumption oftraditional medicine, herbal medicine is likely to increase in the globalization era. Producer/entrepreneur before distributing traditional medicinal products to the public, have to meetrequirements the production and distribution of traditional medicine in order not to contrary tothe conditions set by the Minister of Health and the National Agency of Food and Drug (FDA).In order to protect the public as consumers of traditional medicine circulation of hazardousmaterial have a risk to the public health as a consumer. In order to provide protection to thepublic as consumers of traditional medicine, the government especially the Ministry of Healthand the National Agency of Drug and Food has been set in the Regulation of the Minister ofHealth of the Republic of Indonesia Number 246/Menkes/Per/V/1990. About Industrial BusinessLicence and registration of Traditional Medicines, and Decree of the Minister of Health No.659/MenKes/SK/V/1991 About How To Make Traditional medicine (CPOTB). Although therehave been such an arrangement, as consumers should be more vigilant and not easy to trust oftraditional medicine product advertisement as well as consumers should have the awareness ofthe rights owned and more thoroughly before making a decision to purchase and consumetraditional medicine.
Keywords: entrepreneur, traditional medicine